METODE PENYULUH AGAMA ISLAM DALAM MENGANTISIPASI TERJADINYA PERCERAIAN DI KUA KECAMATAN RILAU ALE KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This research raises the subject of the problem of "how do Islamic Religious Extension Workers anticipate the occurrence of divorce in KUA, Rilau Ale District, Bulukumba Regency" with sub-problems: 1. How do Islamic Religious Extension Workers anticipate the occurrence of divorce in KUA, Rilau Ale District, Bulukumba Regency?. 2. What are the results of how Islamic Religious Extension Workers anticipate divorce in KUA, Rilau Ale District, Bulukumba Regency? This research uses a type of qualitative research, located in KUA, Rilau Ale District, Bulukumba Regency, using an Islamic Extension guidance approach. The methods used in data collection are observation, interviews, and documentation. Data analysis is carried out through three stages: data reduction, data presentation, and conclusion. The results of this study show that the way Islamic Religious Extension Workers anticipating divorce in Rilau Ale District, Bulukumba Regency is by conducting counseling for premarital and post-marriage couples, maximizing counseling both in groups and independently and providing consultation space from the extension workers to taklim council participants. The results of the way Islamic Religious Extension Workers anticipate divorce in KUA, Rilau Ale District, Bulukumba Regency, namely: couples better understand and realize their responsibilities in marriage, a consistent decrease in divorce rates, and a decrease in the level of domestic violence (KDRT). The implications of this study are as follows: 1. It is hoped that Islamic Religious Extension Workers can further maximize their understanding through counseling to anticipate the occurrence of divorce in KUA, Rilau Ale District, Bulukumba Regency. 2. The community, especially prospective brides and married couples, should routinely participate in counseling activities both in groups and participating in counseling through taklim council activities so that it is hoped that couples will be better able to understand their responsibilities and be able to overcome problems in their households, and are also expected to be married couples who are experiencing problems in their households so that they can make good use of the role of extension workers to find the best solution